The Combination of Scutellaria baicalensis Georgi and Sophora japonica L. ameliorate Renal Function by Regulating Gut Microbiota in Spontaneously Hypertensive Rats - Guan, Yiqing; Chen, Kai; Quan, Dongling; Kang, Liangqi; Yang, Danni; Wu, Huanxian; Yan, Mengqiu; Wu, Shaoyu; Lv, Lin; Zhang, Guohua (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is becoming a notable health concern globally. The combination of Scutellaria baicalensis Georgi (SB) and Sophora japonica L. (SJ) has been demonstrated to have anti-hypertensive effects and improve kidney injury clinically. This study aimed to explore the renal protective effect of the combination of SB and SJ against CKD and clarify the potential mechanisms. Male spontaneously hypertensive rats (SHR) were used to induce hypertensive nephropathy and were treated with SB or SJ separately or in combination for 15 weeks, and an antibiotic group was used for a rescue experiment. Blood pressure, serum or urine biochemical markers, serum inflammation factors, short-chain fatty acids (SCFAs), indoxyl sulfate (IS), and oxidative stress indicators were assessed. The mRNA expression of the SCFA receptors olfactory 78 (Olfr78) and G protein-coupled receptor 41 (GPR41) was determined by quantitative real-time PCR. Western blot analysis was performed to determine the expression of intestinal tight junction proteins, including occludin and ZO-1. Gut microbiota profiles were established via high-throughput sequencing of the V3-V4 region of the bacterial 16S rRNA gene. SB and SJ significantly ameliorated the severity of renal injury induced by hypertension. The combination also decreased the ratio of Firmicutes/Bacteroidetes, increased the relative abundance of Lactobacillus, and reduced that of Clostridiaceae. The intestinal barrier was improved, and the change in dominant bacteria reduced IS accumulation and further inhibited oxidative stress activation in kidneys. SB and SJ increased SCFA contents, inhibited inflammatory factor release, and regulated blood pressure by decreasing the expression of Olfr78 and increasing that of GPR41 to alleviate blood pressure-induced kidney damage. This research demonstrated the positive effects of SB and SJ in a rat model of hypertensive nephropathy, indicating that the combination possibly acts by improving the intestinal barrier function, increasing SCFAs, reducing inflammation, decreasing IS, and inhibiting oxidative stress reactions.